Modeling and Simulation of the Lifetime of Saturated Batteries in Real Operating Conditions - VODOUNNOU, Edmond; NOUNANGNONHOU, Cossi Télesphore; AHOUANSOU, ROGER H.; SEMASSOU, GUY CLARENCE (My University, 2023)
This work consists of predicting the lifetime of stationary batteries, in particular the lead acid battery, under real operating conditions. This was made possible by the mathematical model of Schiffer et al, which takes into account the corrosion, degradation of the active material, depth of discharge, acid stratification, and gassing that take place inside the battery during its operation. The model determines the remaining capacity coefficient of the battery for a given operating time. This coefficient allowed to deduce the end of life of the battery. Indeed, the battery is at the end of its life when its remaining capacity is to 20% of the initial value of its capacity. The simulation results show that over 5 years of simulation, the capacity coefficient of the battery studied drops from 1.75 to 0.35 after 3 years 153 days of operation, i.e. 20% of the initial capacity coefficient (1.75), which allows to conclude that the end of life of this battery is reached after 3 years 153 days of operation.
Keywords: Renewable energies; energy storage; lead-acid batteries; continuous power supply; battery life under real operating conditions